Metabonomic Analysis of the Therapeutic Effects of Chinese Medicine Sanqi Oral Solution on Rats With Exhaustive Exercise - Xu, Peng; Li, Shasha; Tian, Ruimin; Han, Ling; Mao, Wei; Li, Li; Li, Chuang; Wang, Yiming; Luo, Guoan; Yang, Nizhi (Frontiers in Pharmacology, 2019)
Exhaustive exercise has emerged as an important health issue nowadays. This study was designed to assess the metabolite abnormalities of rats after exhaustive exercise and the holistic efficacy of Chinese medicine Sanqi oral solution (SQ). Through exhaustive swimming, the exhaustive exercise model in rats was established. Thirty male Sprague–Dawley rats were randomly divided into control, model, and treatment groups. SQ (12 mL•kg-1•d-1) or 0.9% saline solution (control) were administrated orally by gastric gavage. After four weeks, serum samples were collected for biochemical measurements and UPLC/Q-TOF-MS-based metabonomic study. It was found that rats with SQ intervention showed longer exhaustive swimming time (P < 0.05) than model rats, with an average of 1160.36±123.89 s in SQ group and 906.57±172.11 s in model group respectively. Among the biochemical indices, the levels of creatine kinase isoenzyme, lactate dehydrogenase, and glucose of exhaustice exercise rats increased, whereas levels of creatine kinase, urea, triglyceride, and total cholesterol decreased. These biochemical indices came normal after SQ administration, except for triglyceride. Twenty-seven potential biomarkers belonging to sphingolipids, phospholipids, fatty acids, amino acid, and other classes were identified in serum. This study indicated that SQ exerted protective effects on exhaustive exercise by significantly prolonging the swimming endurance time. The metabonomic-based findings of the metabolic state and analysis of potential biomarkers in serum well correlated with biochemical assessment, confirming that SQ had a definite efficacy. Moreover, the shifts in lipid-related metabolites and glycolytic pathway suggested that SQ may serve as a potential sports nutrition supplementation for its pharmacological effect of regulating energy metabolism as well as improving signal transduction and muscle-cell physiological functions.